2010
DOI: 10.1002/dvdy.22360
|View full text |Cite
|
Sign up to set email alerts
|

Regional expression of the ADAMs in developing chicken cochlea

Abstract: The expression patterns of five members of the ADAM (a disintegrin and metalloprotease) family including ADAM9, ADAM10, ADAM17, ADAM22, and ADAM23 were analyzed in different anatomical structures of the developing chicken cochlea by in situ hybridization and immunohistochemistry. Results show that ADAM9, ADAM10, and ADAM17 are widely expressed in the sensory epithelium of the basilar papilla, by homogene cells, spindle-shaped cells, and acoustic ganglion cells, and in the tegmentum vasculosum, each with a diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…Fox example, ADAM9 is transcribed in homogene cells, which play a role in the formation of the tectorial membrane. ADAM10 and ADAM17 are expressed by hair cells, while ADAM22 is found in spindle‐shape cells from E11 (Yan et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Fox example, ADAM9 is transcribed in homogene cells, which play a role in the formation of the tectorial membrane. ADAM10 and ADAM17 are expressed by hair cells, while ADAM22 is found in spindle‐shape cells from E11 (Yan et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Jorissen et al (2010) reported that absence of ADAM10 in mouse induces a premature differentiation of neural progenitor cells into postmitotic neurons in the neocortex. Furthermore, the expression of the ADAMs including ADAM9, ADAM10, ADAM17, ADAM19, ADAM22 and ADAM23 are spatiotemporally expressed in the differentiating sensory neurons of dorsal root ganglia and acoustic ganglion cells of the cochlea Yan et al 2010Yan et al , 2011.…”
Section: Expression Of Adams In the Equatorial Lens Epithelium And Lementioning
confidence: 99%
“…Our previous studies showed that several ADAMs are expressed in the developing chicken brain, spinal cord and cochlea (Lin et al 2008Yan et al 2010). However, little is known about the expression of ADAMs during lens development.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous study has shown that the seven ADAMs, including ADAM9, ADAM10, ADAM12, ADAM13, ADAM17, ADAM22 and ADAM23, are expressed in the developing chicken cochlea at later stage from embryonic day (E) 11 to E18 (Yan et al . ). However, little is known about the expression of these ADAMs at the early stages of the developing cochlea.…”
Section: Introductionmentioning
confidence: 97%